Framing Flood News in Online Media: Comparing Local and National Narratives from an Islamic Perspective - Sekar Arum Mandalia; Muhammad Iqbal; Ingrid Felicia; Akhyar Rifani; Salsabila Imani Putri (UIN Sunan Gunung Djati Bandung, 2026)
This study analyzes differences in flood news framing between local and national online media in South Sumatra, focusing on Sriwijaya Post and Kompas.com during 2025. It examines how both media construct disaster causality, assign responsibility, and formulate solutions using the concepts of media framing, disaster communication, environmental journalism, and the social construction of reality. This qualitative research applies Pan and Kosicki’s framing analysis model, covering syntactic, script, thematic, and rhetorical structures. The research analyzes 80 flood-related news articles published from January to November 2025. The findings show that Kompas.com frames floods as hydrometeorological disasters caused by extreme rainfall and climate anomalies, emphasizing scientific authority, meteorological data, and technocratic policy responses. In contrast, Sriwijaya Post highlights environmental degradation, deforestation, land conversion, and the socio-economic impacts on local communities, constructing a more ecological and humanitarian perspective. The study demonstrates that editorial orientation and geographical proximity significantly influence representations of disasters, ecological responsibility, and governance failures. The main limitations include restricted access to newsroom production processes and the interpretative subjectivity of framing analysis. Rapid digital information flows also make media narratives highly dynamic and context-dependent. Therefore, the study recommends strengthening disaster journalism that prioritizes ecological education, disaster risk mitigation, and public environmental awareness rather than event-centered reporting. This research contributes to disaster communication and media framing studies by demonstrating that local and national media construct disaster realities through different ideological and epistemological orientations, shaping public understanding of ecological crises, environmental governance, and social responsibility in Indonesia.